Kienböck's disease: a case report - Omor, Youssef (Pan Afr Med J, 2015)
Kienböck disease is a condition characterized by avascular necrosis of the lunate bone. Advanced imaging can aid in the diagnosis and staging of Kienböck disease. Magnetic resonance imaging (MRI) is an important adjunct to diagnosis. In particular, MRI is helpful early in the disease when plain radiographs may not reveal abnormalities. A 17 -year-old man with Kienböck disease who underwent radiography and MR is described in this article.